Development of Muara Takus Temple Augmented Reality as a History Learning Media to Improve Reading Skills in Historical Sources - Bunari, Bunari; Fikri, Asyrul; Yuliska, Yuliska (STKIP Singkawang, 2024)
This research aims to develop learning media based on Augmented Reality (AR) which helps students improve their reading skills in historical sources. This research uses the 4D research and development (R&D) method which consists of four stages, namely define, design, develop and disseminate. The sample of research subjects consisted of 3 material, media and language validator experts, 2 teachers, 60 and 120 class X students who assessed the practicality and effectiveness of the product being developed. Data was collected through expert validation, interviews with teachers, teacher and student response tests, and tests on students. while the N-Gain test is to evaluate media effectiveness. Expert validation results show that the criteria are very valid with an average score of 3.78. The teacher and student response test showed an average score of 3.90, which shows that AR media is practically used for learning history. The N-Gain Test score of 75% shows that students' ability to read historical sources is increasing. Therefore, using AR to develop historical source reading skills is feasible, practical, and useful.